1990
DOI: 10.1128/mcb.10.11.5865
|View full text |Cite
|
Sign up to set email alerts
|

RNA processing is a limiting step for murine tumor necrosis factor beta expression in response to interleukin-2.

Abstract: We have previously reported that tumor necrosis factor I8 (TNFO) expression is induced by interleukin-2 (IL-2) in the murine lymphocytic T-cell line CTLL-2. In this study, we have characterized the nuclear and cytoplasmic TNFi transcripts and assessed their role in TNF(8 gene expression. A unique feature of TNFji expression was the accumulation of nuclear precursors, which reflected a slow nuclear RNA processing. As a consequence, there was a delay in the appearance of cytoplasmic messengers after the transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 49 publications
(34 reference statements)
1
41
0
Order By: Relevance
“…Rabbit b-globin and murine LT-a were chosen to investigate the behavior of the nuclear pool of mature mRNAs after arrest of transcription+ Both genes are not naturally expressed in fibroblasts, and their expression in transfected NIH3T3 cells has been previously characterized (Fig+ 1; Neel et al+, 1995)+ b-globin contains two introns, both of them being spliced out efficiently; the cytoplasmic half-life of b-globin mRNA has been reported to be on the order of 11 h in fibroblastic cells (Schiavi et al+, 1994)+ LT-a contains three introns, which are sequentially removed according to a 59-to-39 polarity (Weil et al+, 1990)+ In addition, splicing of intron 3 is slower than that of introns 1 and 2+ Fully spliced mRNA (designated as N0 in Fig+ 1) as well as intron 3-containing transcripts (designated as N1 in Fig+ 1) are exported to the cytoplasm+ Both cytoplasmic transcripts (C0 and C1 in Fig+ 1) have a half-life of 90 min in the T lymphocytic cell line CTLL-2 (Weil et al+, 1990)+ For both genes the complete transcribed region, including the introns, was inserted in an expression vector under the control of a Tet promoter (Dirks et al+, 1994)+ These vectors were stably transfected into the NIHtTA-16-3 cell line (a kind gift of A+ Kröger) that constitutively expresses the chimeric VP16-tTA transactivator allowing for negative regulation by tetracycline (Tet-off system) (Gossen & Bujard, 1992)+ Independent clones were isolated and screened for their level of expression of b-globin or LT-a mRNA+ Clones with a high expression level in the absence of tetracycline (hereafter designated tTA-b-glo and tTA-LT-a) were further characterized+…”
Section: Tetracycline-dependent Expression Of B-globin and Lt-a Genesmentioning
confidence: 99%
See 2 more Smart Citations
“…Rabbit b-globin and murine LT-a were chosen to investigate the behavior of the nuclear pool of mature mRNAs after arrest of transcription+ Both genes are not naturally expressed in fibroblasts, and their expression in transfected NIH3T3 cells has been previously characterized (Fig+ 1; Neel et al+, 1995)+ b-globin contains two introns, both of them being spliced out efficiently; the cytoplasmic half-life of b-globin mRNA has been reported to be on the order of 11 h in fibroblastic cells (Schiavi et al+, 1994)+ LT-a contains three introns, which are sequentially removed according to a 59-to-39 polarity (Weil et al+, 1990)+ In addition, splicing of intron 3 is slower than that of introns 1 and 2+ Fully spliced mRNA (designated as N0 in Fig+ 1) as well as intron 3-containing transcripts (designated as N1 in Fig+ 1) are exported to the cytoplasm+ Both cytoplasmic transcripts (C0 and C1 in Fig+ 1) have a half-life of 90 min in the T lymphocytic cell line CTLL-2 (Weil et al+, 1990)+ For both genes the complete transcribed region, including the introns, was inserted in an expression vector under the control of a Tet promoter (Dirks et al+, 1994)+ These vectors were stably transfected into the NIHtTA-16-3 cell line (a kind gift of A+ Kröger) that constitutively expresses the chimeric VP16-tTA transactivator allowing for negative regulation by tetracycline (Tet-off system) (Gossen & Bujard, 1992)+ Independent clones were isolated and screened for their level of expression of b-globin or LT-a mRNA+ Clones with a high expression level in the absence of tetracycline (hereafter designated tTA-b-glo and tTA-LT-a) were further characterized+…”
Section: Tetracycline-dependent Expression Of B-globin and Lt-a Genesmentioning
confidence: 99%
“…Regulation of LT-a expression by tetracycline+ A: RNase protection assay analysis+ tTA-LT-a cells were treated with indicated tetracycline concentrations for 20 h+ Equal amounts of nuclear (N) and cytoplasmic (C) RNA were analyzed using the LT-a probe represented in Figure 1+ Migration of the riboprobe fragments protected by partially and fully spliced transcripts is indicated on the right+ See Figure 1 for nomenclature of the transcripts+ Unexpected protected fragments are indicated with asterisks+ B: Quantification of cytoplasmic LT-a mRNA+ LT-a signals were quantified using a Molecular Dynamics Storm analyzer, corrected for the number of labeled uridine in each fragment, and plotted as a function of tetracycline concentration+ Concentration of mRNA samples was first checked by Northern blot analysis with b-actin probe+ Note that both axes are on a logarithmic scale+ experiment was performed on tTA-LT-a cells (Fig+ 3A, Tet 0 mg/mL)+ Fully spliced LT-a mRNA was more abundant in the nuclear fraction than in the cytoplasmic one (1+8-fold), so that 17% of the fully mature mRNA of the cell is nuclear+ In contrast to b-globin, and as previously described (Weil et al+, 1990;Neel et al+, 1995), LT-a partially spliced transcripts (N2, N3, and N1) could be readily observed in the nuclear fraction, indicating limiting rates of splicing+ For comparison, the nucleocytoplasmic partition of an endogenous gene was also analyzed and 17% of actin mRNA was found in the nucleus+…”
Section: Characterization Of Nuclear Fractionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This gene constitutes a convenient reporter for premRNA processing studies (Neel et al, 1993(Neel et al, , 1995Weil et al, 1990) because of its short size, moderate level of splicing complexity (three introns which are sequentially removed from the polyadenylated primary transcript), ine cient splicing of intron 3 and the export to the cytoplasm of intron 3 containing precursors as well as fully mature mRNA ( Figure 1b). RNase protection assays can be used to unambiguously identify the di erent RNA species and reliably quantitate their accumulation.…”
Section: Resultsmentioning
confidence: 99%
“…Several cases of intron retention has been reported in the literature [28][29][30][31]. Retained introns could maintain the open reading frame and result in an alternate protein [29,30].…”
Section: Resultsmentioning
confidence: 99%